Understanding Social-Ecological Challenges of a Small-Scale Hilsa (Tenualosa ilisha) Fishery in Bangladesh - Mozumder, Mohammad Mojibul Hoque (Int J Environ Res Public Health, 2019)
Small-scale fisheries (SSFs) have been playing a crucial role in meeting the basic needs of millions of people around the world. Despite this, the sustainability of global fisheries is a growing concern, and the factors enabling or constraining the sustainable management of small-scale fisheries remain poorly understood. Hilsa shad (Tenualosa ilisha) is the single most valuable species harvested in Bangladesh waters, serves nutrition, income, and employment to the large population. This study analyzed the state and challenges of hilsa fishery in the Gangetic River systems (Padma and Meghna Rivers) by using two frameworks, namely the social-ecological systems (SES) and drivers-pressure-state-impact-responses (DPSIR) frameworks. Primary data for this analysis were collected by in-depth interviews (n = 130) and focus group discussions (n = 8) with various stakeholders in the hilsa fisheries. The perspectives explored here have been both critical and constructive, including the identification of problems and suggestions for improving the management of this particular social-ecological system. Hilsa fisheries, however, have come under severe threat since 2003 because of population growth, overfishing, pollution, climate change, the disruption of migration routes due to siltation, etc. All these have caused reduced catches and less stable incomes for fishers. This, in turn, has led to poverty, malnutrition, social tensions, stakeholder conflicts, and debt cycles amongst more impoverished fishing communities. These problems have been compounded by improved fishing technology amongst larger-scale ventures, the use of illegal fishing gears, and the non-compliance of government fishery management programs. Recommendations include the promotion of community-supported fisheries, the enhancement of stakeholder’s social resilience, the introduction of co-management approach, an increase in incentives and formal financial supports, and possible community-managed sustainable ecotourism including hilsa fishing-based tourism.